Rotating machinery, hybrid test methods, vibro-acoustics & laser vibrometry. Volume 8 : proceedings of the 35th IMAC, a Conference and Exposition on Structural Dynamics 2017 - Di Maio, Dario; Castellini, Paolo (Conference proceedings of the Society for Experimental Mechanics series., 2017)
Rotating Machinery, Hybrid Testing, Vibro-Acoustics & Laser Vibrometry, Volume 8: Proceedings of the 35th IMAC, A Conference and Exposition on Structural Dynamics, 2017, the eighth volume of ten from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Rotating Machinery, Hybrid Testing, Vibro-Acoustics & Laser Vibrometry, including papers on: Rotating Machinery Vibro-Acoustics Experimental Techniques Advances in Wind Energy Scanning Laser Doppler Vibrometry Methods Hybrid Test Methods.